OPTIMALISASI PEMANFAATAN AIR BAWAH TANAH UNTUK PENINGKATAN PRODUKTIVITAS PANGAN DI KECAMATAN KEDUNGTUBAN BLORA - Hariyanto Hariyanto; Subandi Subandi (SIMETRIS, 2014)
Availability of water for irrigation in Sub Kedungtuban Blora very limited, in order to meet the water requirements for crops, the use of groundwater for irrigation is needed by farmers by providing capacity resources (people, equipment, materials) available, the necessary ability in utilization of water land for optimal irrigation. The main objective to be achieved is to know the amount of underground water point for irrigation water flow on irrigation and crop kebutuan especially corn, soybean and rice farmer in the district obtained Kedungtuban District. Blora and as a reference for the optimization and development of the wider utilization of underground water.Method used is descriptive method, a method that is designed to collect a variety of information about the circumstances that are going on, the way to determine the point of field surve underground water used, water flow, water demand fields, crop yields for farmers 17 villages . Sampling was done every village allotment quota sampling 5 total sample of 85 farmers deemed capable of representing the farmers.Crop farmers in the district of 17 villages taken Kedungtuban 5 representatives of farmers showed that the rice and maize yields in the last 5 years ie acquisition in 2009 (5.6 tons), in 2010 (5.6 tons), in 2011 (5, 6 tons), in 2012 (5.6 tons), in 2013 (5.6 tons) 5 area farmers average (1.04 ha) of the results of the maximum Keith prodoktivitas crops. Farmers who use groundwater number 57 farmers (67.06%) in eleven villages include Bajo, Gondel, Jimbung, Kemantren, Klagen, Pulo, Sidorejo, Cape, Wado, Panolan and Sogo. Rainfed area 22 farmers (25.88%) in five villages include Kalen village, Galuk, Kedungtuban, Nglandean and Ngraho and farmers who use the water flow Sunga by using a water pump 6 farmers (7:06%) in the two villages that cover ketuan and Jimbung, while average groundwater produced is 12.5 liters / sec.